How Republicans and Democrats Strengthen Secret Surveillance in the United States - Laidler, Paweł (Political Preferences, 2020)
The purpose of the paper is to assess the relationship between secrecy and transparency in the pre- and post-Snowden eras in the United States. The Author analyzes, from both political and legal perspectives, the sources and outcomes of the U.S. politics of national security with a special focus on domestic and intelligence surveillance measures. The core argument of the paper is that, due to the role of the executive which has always promoted the culture of secrecy, there is no chance for the demanded transparency in national security surveillance, despite the controlling powers of the legislative and judiciary. As the analysis proves, the United States in the post-Snowden era seems to be the most transparent and secretive state, at the same time.